2020
DOI: 10.1007/s11033-020-05806-8
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram as a modulator of proopiomelanocortin, kisspeptin, Kiss1R and MCHR1 gene expressions in the male rat brain

Abstract: Neuropeptides are important, multifunctional regulatory factors of the nervous system, being considered as a novel, atypical sites of antidepressants action. It has already been proven that some of them, such as selective serotonin reuptake inhibitors (SSRI), are able to affect peptidergic pathways in various brain regions. Despite these reports, there is so far no reports regarding the effect of treatment with SSRIs on brain proopiomelanocortin (POMC), kisspeptin, Kiss1R and MCHR1 gene expression. In the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…2). This finding appears to be in keeping with our previous results showing elevated proopiomelanocortin (POMC) and kisspeptin receptor Kiss1 mRNA levels in the rat hypothalamus after chronic escitalopram administration (Pałasz et al 2020). A distinct population of intensively NPS positive cells are observed almost exclusively within the brainstem (posterodorsal tegmental nucleus, locus coeruleus, parabrachial nucleus) and cerebellum (Purkinje cells and dentate nucleus).…”
Section: Resultssupporting
confidence: 92%
“…2). This finding appears to be in keeping with our previous results showing elevated proopiomelanocortin (POMC) and kisspeptin receptor Kiss1 mRNA levels in the rat hypothalamus after chronic escitalopram administration (Pałasz et al 2020). A distinct population of intensively NPS positive cells are observed almost exclusively within the brainstem (posterodorsal tegmental nucleus, locus coeruleus, parabrachial nucleus) and cerebellum (Purkinje cells and dentate nucleus).…”
Section: Resultssupporting
confidence: 92%
“…NPSRs, which are the target proteins of NPS, are distributed in various serotonin-dependent areas [11] , [12] , [20] , which is why an effect on their modulation might have significance for the mechanism of action of escitalopram. Experimental studies have indicated that when escitalopram is given chronically, it alters the mRNA levels of various neuropeptides in the brainstem [26] , [27] , [91] and in the other brain structures [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Escitalopram interacts with both the orthosteric and allosteric sites of the serotonin transporter (SERT) and enhances serotonin transmission, which is thought to be the basis for its therapeutic effects [25] . Recently, evidence that escitalopram alters the NPQ/SPX mRNA expression [26] , proopiomelanocortin (POMC) [27] and OX-A [28] was found in the rat hypothalamus. Venlafaxine is frequently used in the therapy of moderate-to-severe depression and generalized anxiety disorder and phobias [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Given the interaction between kisspeptin and the serotonergic system, it is interesting to consider the brain regions involved in eliciting the antidepressant-like effects. In a recent study, adult male rats received four weeks of intraperitoneal escitalopram ( 92 ), a widely prescribed selective serotonin reuptake inhibitor for mood disorders, which increases serotonin activity in the brain by limiting its reabsorption. This experimental paradigm significantly upregulated Kiss1 mRNA expression in the amygdala (272% increase compared to saline treated rats).…”
Section: Mood and Emotionsmentioning
confidence: 99%
“…This experimental paradigm significantly upregulated Kiss1 mRNA expression in the amygdala (272% increase compared to saline treated rats). Furthermore, Kiss1r mRNA was highly increased in the hypothalamus, hippocampus and cerebellum by 170%, 177% and 131%, respectively ( 92 ). Indeed, these findings are congruent with a previous study demonstrating that intra-cerebroventricular injections of serotonin hydrochloride to male rats significantly enhances hypothalamic kisspeptin expression and resultant circulating LH concentrations ( 93 ).…”
Section: Mood and Emotionsmentioning
confidence: 99%